`Respect for Religious Feelings': As the Italian Case Shows, Fresh Paint Can't Fix the Crumbling Wall of Blasphemy - Tommaso Virgili (European Public Law, 2022)
This article examines the relation between free speech and blasphemy laws and assesses whether the latter may still have a place in secular, liberal democracies. After a theoretical introduction on free speech, its function in a liberal society and the possible grounds for restrictions, the analysis will focus on Italy – prototypical case of a country that has experimented with diverse ways of outlawing blasphemy. The article argues that blasphemy laws, even when wrapped in the new clothes of the `protection for religious feelings', perpetuate a favour toward institutionalized religions that is hardly justifiable today from a constitutional or even logical perspective. The privilege enjoyed by stronger religious denominations, the discrimination between different expressions of individual conscience, the chilling effect on free speech in the name of dogmas – these are all issues of serious concern inextricably linked to blasphemy laws that are intolerable in secular, liberal democratic societies. blasphemy, free speech, freedom of expression, religious feelings, religious sensibilities, freedom of religion, Italy
Keywords: 300; blasphemy; free speech; freedom of expression; religious feelings; freedom of religion; Italy; religious sensibilities